Comparative Design and Analysis of Helical and Wave Spring - Muralidharan, M; Aravinth, R; Gafferkhan, J; Gandhi, R (International Journal of Engineering and Technology, 2018)
This paper is a comparative between two springs such as helical and wave spring. Wave springs are precise flat wire compression springs that fit into assemblies that other springs cannot. These are used as an alternative spring for helical spring. Wave springs provide 50% reduction in spring height and axial space. They possess the same force and deflection as coil springs. They have reduced material requirements. They provide improved cost reduction. The Wave Spring has been subjected to Compression Test, Modal Analysis and Equivalent Elastic Strain Test and then compared to Helical Spring which again was subjected to the above same tests under the same conditions and parameters. The design of helical spring and wave spring has been done in CREO Parametric 4.0 and analysed in ANSYS R 18.1. The results are then compared.Â Â